A Trust Proxy Node (TPN) Based Black hole Attack Detection Mechanism in MANET Using AODV - Saraf, Amit; Singh, Megha (International Journal of Computer Sciences and Engineering, 2025)
A mobile ad hoc network (MANET) is auto-configuring network without any infrastructure. It is temporary network created by, mobile nodes which are capable to communicating with each other without the use of network infrastructure. Ad hoc networks are vulnerable to many type of security attacks due to their open medium, dynamic topology, distributed co-operation. For successful data transfer nodes are depend on each other. To believe on the other node for wireless data transmission, consider as trust problem. Our aim in this review is to present schemes which are mainly focused on security based on trust value of node in MANET. This work proposes a approach for trust calculation based on Trust proxy node (TPN). The route discovery is achieved through a routing decision based on trust sequence certificate exchange by Trust proxy node (TPN). Trust proxy node (TPN) is an additional node having extra responsibility for trust calculation of Black hole node. Trust proxy node (TPN) will act as monitoring node for routing decision. After the trust value index is calculated the TPN node issues a certificate to every node in its network. To participate in routing the nodes must have two trust index (TI) certificates & can be consider as a reliable node by TPN. The directory of this certificate is maintained in a Trust Index (TI) Table. This TI table is shared with the server by this centralized TPN. This TPN will also monitors the behavior of nodes in a specific range continuously to avoid unwanted action